Synthesis, Characterization and the Solvent Effects on Interfacial Phenomena of Jatropha Curcas Oil Based Non-Isocyanate Polyurethane - Haniffa, M.A.C.M.; Ching, Yern Chee; Chuah, Cheng Hock; Kuan, Y.C.; Liu, D.S.; Liou, N.S. (MDPI, 2017)
Non-isocyanate polyurethane (NIPU) was prepared from Jatropha curcas oil (JCO) and its alkyd resin via curing with different diamines. The isocyanate-free approach is a green chemistry route, wherein carbon dioxide conversion plays a major role in NIPU preparation. Catalytic carbon dioxide ﬁxation can be achieved through carbonation of epoxidized derivatives of JCO. In this study, 1, 3-diaminopropane (DM) and isophorone diamine (IPDA) were used as curing agents separately. Cyclic carbonate conversion was catalyzed by tetrabutylammonium bromide. After epoxy conversion, carbonated JCO (CJCO) and carbonated alkyd resin (CC-AR) with carbonate contents of 24.9 and 20.2 wt %, respectively, were obtained. The molecular weight of CJCO and CC-AR were determined by gel permeation chromatography. JCO carbonates were cured with different amine contents. CJCO was blended with different weight ratios of CC-AR to improve its characteristics. The cured NIPU ﬁlm was characterized by spectroscopic techniques, differential scanning calorimetry, and a universal testing machine. Field emission scanning electron microscopy was used to analyze the morphology of the NIPU ﬁlm before and after solvent treatment. The solvent effects on the NIPU ﬁlm interfacial surface were investigated with water, 30%ethanol, methyl ethyl ketone, 10%HCl, 10%NaCl, and 5%NaOH. NIPU based on CCJO and CC-AR (ratio of 1:3) with IPDA crosslink exhibits high glass transition temperature (44 ◦C), better solvent and chemical resistance, and Young's modulus (680 MPa) compared with the blend crosslinked with DM. Thus, this study showed that the presence of CC-AR in CJCO-based NIPU can improve the thermomechanical and chemical resistance performance of the NIPU ﬁlm via a green technology approach.